Effects of Inonotus obliquus Polysaccharides on Proliferation, Invasion, Migration, and Apoptosis of Osteosarcoma Cells - Baohui Su; Xuezhi Yan; Yuezhong Li; Junshan Zhang; Xiaoyan Xia (Analytical Cellular Pathology)
Objectives. To observe the effect of Inonotus obliquus polysaccharide (IOP) on the proliferation, invasion, migration, and apoptosis of osteosarcoma cells and to elucidate its underlying molecular mechanism. Methods. IOP was extracted from Inonotus obliquus, human osteosarcoma MG-63 cells and U2OS cells were cultured in vitro, and the effects of IOP on the proliferation, migration, invasion, and apoptosis of MG-63 cells and U2OS cells were determined by CCK-8 assays, cell scratch assays, transwell assays, and flow cytometry, respectively. Western blot was used to detect the expression of related proteins in the Akt/mTOR and NF-κB signaling pathways. Results. Compared with the control group, MG-63 cells and U2OS cells treated with IOP of 80 μg/ml, 160 μg/ml, and 320 μ g/ml in the experimental group had significantly lower proliferation activity, decreased migration and invasion ability, and increased apoptosis rate (P<0.05). Furthermore, IOP could significantly inhibit the activation of the Akt/mTOR and NF-κB signaling pathway (P<0.05). Conclusion. IOP can regulate the proliferation, migration, invasion, and apoptosis of osteosarcoma cells by inhibiting the activation of the Akt/mTOR signaling pathway. It has antitumor activity on osteosarcoma and has the potential of clinical application in osteosarcoma treatment.